2005
DOI: 10.1093/geront/45.4.516
|View full text |Cite
|
Sign up to set email alerts
|

Use of Complementary Medicine in Older Americans: Results From the Health and Retirement Study

Abstract: The magnitude and patterns of CAM use among elders lend considerable importance to this field in public health policy making and suggest a need for further epidemiological research and ongoing awareness efforts for both patients and providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
96
4
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(117 citation statements)
references
References 36 publications
16
96
4
1
Order By: Relevance
“…In these studies, the percentage of CAM usage varies between 35.3% and 86.3% [10][11][12][13][14][15] . In studies carried out on elderly individuals, the percentage of CAM usage varies between 27.7% and 88% 8,[16][17][18][19][20][21][22][23][24][25][26] . These methods have been preferred mostly by elderly who are well-educated 3,16,19 have a high socio-economical status 19,20 , are female 17,19,27,28 , and are younger elderly 16 .…”
Section: Araştirma Makalesi̇ / Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, the percentage of CAM usage varies between 35.3% and 86.3% [10][11][12][13][14][15] . In studies carried out on elderly individuals, the percentage of CAM usage varies between 27.7% and 88% 8,[16][17][18][19][20][21][22][23][24][25][26] . These methods have been preferred mostly by elderly who are well-educated 3,16,19 have a high socio-economical status 19,20 , are female 17,19,27,28 , and are younger elderly 16 .…”
Section: Araştirma Makalesi̇ / Research Articlementioning
confidence: 99%
“…In this study, we have observed that the elderly have used non-herbal supplements such as honey, vitamins (vitamin B, vitamin C, vitamin D, vitamin E, and vitamin A; respectively), fish oil, royal jelly, magnesium, omega 3-6-9, and coenzyme Q10 at rates differing between 7% and 31.7%. Previous studies showed that elderly individuals mostly use vitamin E 18,20 , Ca 20,26 , magnesium 26 , iron 26 , vitamin C 18,20 , vitamin D 3 26 , B 12 26 , folic acid 26 , chondroitin sulphate 18 and minerals 18 . Our study results are in line with the literature.…”
Section: The Frequency Of Cam Usagementioning
confidence: 99%
“…They also argued that differences in CAM use by race must be considered when advising patients. Similarly, support for this position is offered by Ness, Cirillo, Weir, Nisly, and Wallace (2005) and Yoon, Horne, and Adams (2004).…”
Section: Current Researchmentioning
confidence: 97%
“…Yoon et al concluded that indiscriminate use of herbal products, in combination with, or in place of, conventional medicines can be problematic and costly. In another study, Ness et al (2005) studied the use of complementary medicine in older Americans and found African Americans used fewer dietary supplements and fewer chiropractic services, but they reported more personal practices (e.g., breathing exercises, meditation) than Whites.…”
Section: Current Researchmentioning
confidence: 99%
“…25 All existing survey research studies demonstrate that blacks use chiropractic health care services less often than whites. [2][3][4][5][6][7]9,15,16,[26][27][28][29] In many instances, whites used chiropractic at least twice as often as blacks. 2,4,6,7,9,15,16,26,29 Some have attributed this difference to the perception of discrepancies of health care treatment by blacks, lower average educational levels of blacks compared to whites, and the lack of accessibility to doctors of chiropractic (DCs) in black communities.…”
Section: Introductionmentioning
confidence: 99%